A simple approach to prepare self-assembled, nacre-inspired clay/polymer nanocomposites. Issue 23 (3rd June 2020) - Xu, P.; Erdem, T.; Eiser, E.
Abstract : Inspired by the relationship between the ordered architecture of aragonite crystals and biopolymers found in natural nacre, we present a facile strategy to construct organic/inorganic nanocomposites with hierarchical structure via a water-evaporation driven self-assembly process. Abstract : Inspired by the relationship between the well-ordered architecture of aragonite crystals and biopolymers found in natural nacre, we present a facile strategy to construct large-scale organic/inorganic nacre-mimetics with hierarchical structure via a water-evaporation driven self-assembly process. We connect LAPONITE®-nanoclay platelets with each other using carboxymethyl cellulose, a cellulose derivative, thus creating thin, flexible films with a local brick-and-mortar architecture. The dried films show a pronounced resistance against tensile forces allowing for stronger thin films than nacre. In terms of functionalities, we report excellent glass-like transparency along with exceptional shape-persistent flame shielding. We also demonstrate that through metal ion-coordination we can further strengthen the interactions between the polymers and the nanoclays, and thus enhanced mechanical, and thermal properties as well as resistance against swelling and dissolution in aqueous environments. We believe that our simple pathway to fabricate such versatile polymer/clay nanocomposites can open avenues for inexpensive production of environmentally friendly, biomimetic materials in aerospace, wearable electrical devices, and in the food packaging industry.